Acute Device-Related Thrombus after Watchman Device Implant. (3rd September 2019) - Ajmal, Muhammad; Swarup, Vijendra
Abstract : Atrial fibrillation is characterized by irregularly irregular heart rhythm with an increased morbidity and mortality. It is associated with an increased risk of thromboembolism due to formation of blood clot in the left atrium. Most of these blood clots are formed in the left atrial appendage. The risk of blood clot formation is reduced with the use of anticoagulants. The patients who cannot take anticoagulants due to an increased bleeding risk can undergo percutaneous left atrial appendage (LAA) closure. A Watchman device is used for this purpose. LAA closure with the Watchman device is associated with some adverse effects, and one of them is device-related thrombus. Currently, there are no specific guidelines for the management of device-related thrombus. We present a case of Watchman device-related thrombus which developed 16 hours after the device placement. We will also discuss various options for the management of acute thrombosis.